A THE CONCEPT OF TEMPORARY PROTECTION AS A REFUGE PROTECTION MECHANISM IN INTERNATIONAL LAW - Oktay, Hasan; Poposka, Vesna (International Scientific Journal Vision, 2017)
Existing security challenges, armed conflicts, especially civil wars, create enormous displacements. Clear and effective protection mechanisms are necessary to make sure the displaced persons receive suitable protection and states receiving the influx are able to cope with the pressure. Not all persons displaced by an armed conflict can be protected within the Convention Relating to the Status of Refugees, but states have an obligation under customary international law to provide refuge to persons fleeing persecution, torture and immediate harm to their life and physical integrity. This thesis demonstrates that temporary protection can provide a viable background to respond to large scale influx of persons fleeing armed conflict that will cover the protection gaps in the 1951 Convention and the state obligation to provide refuge.